Pengaruh Greed, Opportunity Dan Locus Of Control Terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi (Studi Empirispada Mahasiswa S1 Akuntansi Universitas Muhammadiyah Metro) - Wati, Ade Diana; Suyanto, Suyanto; Rahayu, Sri Retnaning (Universitas Muhammadiyah Metro, 2022)
This study aims to determine: (1) the influence of greed on the academic cheating behaviour of accounting students, (2 the influence of opportunity on the academic cheating behaviour of accounting students, and (3) the influence of Locus of Control on the academic cheating behaviour of accounting students, (4) the influence of Greed, Opportunity, and Locus of Control together on the academic cheating behaviour of accounting students. A questionnaire sampling of 118 samples with research data collection techniques was carried out. The research data were obtained using SPSS version 26 software. The data analysis technique used multiple linear regression analysis techniques and hypothesis testing. The results of this study indicate that: (1) Greed affects academic cheating behaviour, (2) Opportunity has an effect on academic cheating behaviour, (3) Locus of Control has no effect on academic cheating behaviour, (4) Greed, Opportunity, and Locus of Control jointly affect the academic cheating behaviour of accounting students at Muhammadiyah Metro University.